ALIH KODE DAN CAMPUR KODE DALAM FILM ARAB HONEYMOONISH KARYA ELIE EL SEMAAN - Marista Aulia Karima; Rohanda Rohanda; Irfan Adriadi (Universitas Muhammadiyah Surabaya, 2025)
This research aims to describe code-switching and code-mixing in the Arabic movie Honeymoonish by Elie El Semaan by using a qualitative approach and applying analytical descriptive method. The formal object of this research is code switching and code mixing, while the material object is the Arabic movie Honeymoonish. The results and discussion in this study show that all code-switching and code-mixing in this movie belong to the external type because of the switching and insertion of English into the original language, namely Arabic. The form of code mixing found is the form of words and phrases. Based on the results of the analysis, it can be concluded that overall there are 31 data in the form of code switching and external code mixing. There are 3 data of external code switching, 15 data of external code mixing at word level, and 7 data of external code mixing at phrase level. Keywords: Arabic Film, Code Mixing, Code Switching, Sociolinguistics